KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN MASALAH BERBENTUK OPEN START DI SMP NEGERI 2 PONTIANAK - Muzdalifah Muzdalifah; Halini Halini; Dian Ahmad BS (Universitas Tanjungpura, 2017)
AbstractThis research aims to describe the ability of student’s creative thinking in solving open start problems at SMPN 2 Pontianak. Method used was descriptive in form survey. The subject in this research was 36 students of the VIII F class of SMPN 2 Pontianak. Tools of data collection are written test to discover the ability of students’ creative thinking in solving open start problems; and interview to verify the test results. The results of creative thinking ability test show that most students are only able to solve problems using one way correctly, and the way is that teachers teach in the classroom. The ability of students creative thinking is included in the medium category with an average score of 4,16 or 41,67 %. The ability of students to think fluency included in the middle category with an average score is 0,86 or 43,05%. The ability of students to think flexibel included in the middle category with an average score 1,78 or 44,44%. The ability of students to think novelty included in the low category wwith an average score 1,47 or 36,80%.Keywords: Creative Thinking Ability, Open Start Problem